Vitamin C Rescues in vitro Embryonic Development by Correcting Impaired Active DNA Demethylation - Chu, Meiqiang; Yao, Fusheng; Xi, Guangyin; Yang, Jiajun; Zhang, Zhenni; Yang, Qianying; Tian, Jianhui; An, Lei (Frontiers in Cell and Developmental Biology, 2021)
During preimplantation development, a wave of genome-wide DNA demethylation occurs to acquire a hypomethylated genome of the blastocyst. As an essential epigenomic event, postfertilization DNA demethylation is critical to establish full developmental potential. Despite its importance, this process is prone to be disrupted due to environmental perturbations such as manipulation and culture of embryos during in vitro fertilization (IVF), and thus leading to epigenetic errors. However, since the first case of aberrant DNA demethylation reported in IVF embryos, its underlying mechanism remains unclear and the strategy for correcting this error remains unavailable in the past decade. Thus, understanding the mechanism responsible for DNA demethylation defects, may provide a potential approach for preventing or correcting IVF-associated complications. Herein, using mouse and bovine IVF embryos as the model, we reported that ten-eleven translocation (TET)-mediated active DNA demethylation, an important contributor to the postfertilization epigenome reprogramming, was impaired throughout preimplantation development. Focusing on modulation of TET dioxygenases, we found vitamin C and α-ketoglutarate, the well-established important co-factors for stimulating TET enzymatic activity, were synthesized in both embryos and the oviduct during preimplantation development. Accordingly, impaired active DNA demethylation can be corrected by incubation of IVF embryos with vitamin C, and thus improving their lineage differentiation and developmental potential. Together, our data not only provides a promising approach for preventing or correcting IVF-associated epigenetic errors, but also highlights the critical role of small molecules or metabolites from maternal paracrine in finetuning embryonic epigenomic reprogramming during early development.